Program Pelatihan Motivasi Usaha, Sumber Modal Usaha dan Penyusunan Laporan Keuangan bagi Penyandang Disabilitas di Wilayah Kecamatan Sukajadi Kota Bandung - Rudianto, Dudi; Weni Pratiwi, Monica; Zubaidah Chaidir, Siti; Nurusyifa, Nurusyifa (Indonesian Journal for Social Responsibility, 2021)
Handling for persons with disabilities requires assistance and broad community participation so that they can live independently and feel “normal” among other members of the community. These efforts are carried out through business motivation training programs, business plans, sources of business capital and preparation of financial reports facilitated by the Bakrie University Community Service Institute (LPkM) for people with disabilities in the Sukajadi District, Bandung City. The training program was carried out offline for 2 days from 15-16 March 2021 at the Sukajadi District Hall, Bandung City. The participants who attended the training were 18 people with disabilities, consisting of 9 people with physical disabilities, 7 people who were blind and 2 people who were deaf. The training materials consist of business motivation, business plans, sources of venture capital and the preparation of simple financial reports. After participating in this training program, all participants feel the benefits obtained, this result is shown by the post-test scores which are higher than the pre-test scores for all training materials, each increasing 40% for business motivation materials, 30% for planning materials business, 60% for business capital sources and 40% for financial statement preparation materials. Likewise, the participants' increased desire to receive follow-up from the training program in the form of mentoring to become real entrepreneurs. This desire is shown by video testimonials from participant representatives and the active participation of participants in the WhatsApp Group whose members are fellow trainees and all resource persons, as a means of discussion and information. One of the results of the implementation of this training activity, one of the training participants joined the MSME convection business to take part in the exhibition held at the Bandung Trade Mall.